Megan Pitcavage and Dana Cohen playing volleyball against MIT - Unknown (Tufts Archival Research Center, 2014)
This date is approximate. 5 x 7 in., photographic print. Back of print reads: "#14 Megan Pitcavage; #2 Dana Cohen; 10/28 vs MIT - Kate Cohen"